Determinants of re-borrowing intention in peer-to-peer lending - Tri Purwani; Harto Listijo; Naziruddin Abdullah (Global Business & Finance Review (GBFR), 2024)
Purpose: This study aims to determine the effect of perceived usefulness, perceived ease of use, and insecurity risk on re-borrowing intention in peer-to-peer lending moderated by the facilitating condition. P2P lending in Indonesia is still at an early stage of development so there are many challenges related to insecurity and public acceptance of P2P lending financial technology. Design/methodology/approach: This study uses a quantitative approach for survey research. The research population was peer-to-peer lending borrower in the Special Region of Yogyakarta, Indonesia. The sample members were 207 online loan borrowers by chance contacted by the researchers in different online loan in Indonesia. The data analysis method used is the Structural Equation Modeling technique based on Partial Least Square. Findings: The study found that perceived usefulness and perceived ease of use, has positive and significant effect on online loan attitude. Insecurity risk has a negative and significant effect on online loan attitude (t-test value of 5.36 and p= 0.03<0.05). Besides, online loan attitude seems proven to have a positive and significant effect on re-borrowing intention. Likewise, effect of online loan attitude on re-borrowing intention moderated by the facilitating condition. Research limitations/implications: This research has several limitations. The variables in this research are developed from the basic TAM model by adding other variables outside TAM. The factors influencing re-borrowing behavior on online loans can differ in different theoretical approaches. Hopefully, future research can compare the results of this study with other models outside TAM. Originality/value: It often encourages irrational decisions by re-borrowing online loans even though they realize this decision is not wise. This article attempts to fill the gap in the literature by adding insecurity factors and facilitating conditions to attitudes and intentions in using technology in the context of online P2P lending from the borrower's side.
Keywords: 650; Re-borrowing intention; Peer-To-Peer lending; Technology acceptance model; Insecurity; Facilitating conditions